An overview of the effects of out‐of‐band interference on GNSS receivers. Issue 1 (14th January 2020) - Hegarty, Christopher J.; Bobyn, Dan; Grabowski, Joe; Van Dierendonck, A.J.
Abstract: This paper addresses the wide range of mechanisms through which out‐of‐band interference can disrupt the functioning of GNSS receivers. These mechanisms include saturation and desensitization of front‐end low noise amplifiers, mixers and other circuitry; reciprocal mixing effects that arise from the fact that receivers cannot generate a perfect tone to down‐convert the desired signals; intermodulation products; aliasing of out‐of‐band emissions that remain after filtering into the receiver's passband; and the reception of in‐band (to GNSS) emissions that are always present due to imperfections in the signal generation and filtering of the interfering system. These mechanisms are described in detail and mitigation approaches for each are discussed.